Implementation of Village Government Apparatus Performance in Public Services to the Community (Malasan Village, Durenan District, Trenggalek Regency) - Salsala Ghosi Ainiha; Lukman Yudho Prakoso (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
The power exercised by the village government requires the apparatus to be able to work well for the surrounding area, but this has not been implemented due to several factors. The aim of this research is to find out how village officials perform in providing public services to the community. Information is obtained through interviews, observations and documentation. The sources decided are the village head, village officials and the local community. The focus of the research is work results (quality and quantity), apparatus capabilities, level of initiative/creativity, behavior, level of punctuality in services and discipline of village officials. The results of the research show that the performance of the Malasan Village Apparatus in public services is not good, this is due to a lack of technological and information knowledge, a lack of initiative and creativity in work, as well as a lack of responsibility and work discipline. So that the completion of work, especially in providing services, is still hampered and has not been completed properly.